2000
DOI: 10.1097/00007632-200008150-00019
|View full text |Cite
|
Sign up to set email alerts
|

Atlantoaxial Subluxation Associated With Ossification of Posterior Longitudinal Ligament of the Cervical Spine

Abstract: Ossification of the posterior longitudinal ligament of the cervical spine may cause atlantoaxial subluxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…16 The occipitoatlantoaxial joint accounts for 45° of flexion and extension. 13 However, in our case, the movement almost disappeared, and it was therefore impossible for the compensatory mechanism of the occiput-C1 joint to function.…”
Section: Discussionmentioning
confidence: 51%
“…16 The occipitoatlantoaxial joint accounts for 45° of flexion and extension. 13 However, in our case, the movement almost disappeared, and it was therefore impossible for the compensatory mechanism of the occiput-C1 joint to function.…”
Section: Discussionmentioning
confidence: 51%
“…1 From the dynamics radiographs, we estimated the patient has no instability at the craniocervical segment 19 , and thus laminectomy from C1 to C3 without occipitoatlantal arthrodesis was performed. The previous reports suggested the necessity of rigid fixation of the cervical spine 20 , but, we had not recognized any further problems without performing arthrodesis in this case.…”
Section: Cervical Myelopathy By Dishmentioning
confidence: 56%
“…They proposed that fusion of the subaxial cervical spine caused the hypermobility at C1–2, and may lead to the ligamentous damage and upper cervical cord compression. In another study, Takasita et al [ 19 ] suggested that OPLL can affect the cervical biomechanics and restricts the mobility of the lower cervical spine, which causes additional mechanical demand on the atlantoaxial joint and subsequently leads to atlantoaxial subluxation. However, some authors disagreed with this hypothesis and proposed the pathology of combined upper cervical cord compression and cervical OPLL is that upper cervical cord compression occasionally occurred in patients with cervical OPLL.…”
Section: Discussionmentioning
confidence: 99%